Identification of Marker Linked with Little Leaf Resistance in Brinjal [Solanum melongena L.] - Chauhan, B. P.; Solanki, Urja B.; Shukla, Y. M.; Pandya, M. M.; Kumar, S.; Mahla, J. S. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during kharif (September, 2023 to February, 2024) at Main Vegetable Research Station, Anand Agricultural University, Anand, Gujarat, India to find out the linked marker to Little leaf disease resistant gene in brinjal. The experimental materials were comprised of F2:3 segregating population of cross resistant parent AB 15–06 and susceptible parent GRB 5 against little leaf disease. Total 168 mapping population were developed from F1 seeds derived from crosses of above refereed parents. F1 hybrid seeds were collected in the year 2020–21. Total 168 F2 mapping population were sown in the year 2021–22. In the year 2022–23, 168 F2 mapping population collected seeds were sown as F2:3 mapping population for morphophysiological characterizations. Phenotyping evaluation study in F2:3 168 mapping population was subjected for morphophysiological characters viz., days to initiation of flowering (24.6–55.4), plant height (62.3–111 cm), primary branches plant-1 (6.8–18.4), leaf length (12.7–24.1 cm), leaf width (7.1–18.3 cm), fruit volume (10–346.8 cc), no. of fruits plant-1 (10.3–55), fruit weight (34.4–95.5 g), fruit yield plant-1 (0.5–3.2 kg) and disease incidence (0–38.3%). Days to initiation of flowering (47), plant height (111 cm), no. of fruits plant-1, fruit weight (35.9 g), fruit yield plant-1 (80.5 kg) were recorded higher in resistant parent. Correlation analysis indicated that morphophysiological traits like days to initiation of flowering and primary branches plant-1 positively correlated with the disease incidence.